2010
DOI: 10.1200/jco.2010.28.18_suppl.2
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel combined with monthly carboplatin versus single-agent therapy in patients age 70 to 89: IFCT-0501 randomized phase III study in advanced non-small cell lung cancer (NSCLC).

Abstract: 2 Background: Incidence of advanced NSCLC in the elderly is increasing. Specific trials for elderly are seldom and those patients are not optimally treated. Current recommendations are monotherapies with gemcitabine or vinorelbine. Methods: French multicentric randomized phase III study in pts aged 70 to 89, PS 0-2 with advanced NSCLC not irradiable, comparing a 3-weekly single agent therapy (gemcitabine 1,150 mg/m2 or vinorelbine 30 mg/m2, d1, d8: arm A) with carboplatin AUC 6 every 4 weeks + paclitaxel 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…In NSCLC, four randomized studies have explored the use of chemotherapy in the elderly (53)(54)(55)(56). The ELVIS trial demonstrated that single agent vinorelbine increased survival and quality of life over best supportive care (53).…”
Section: Clinical Protocolsmentioning
confidence: 99%
“…In NSCLC, four randomized studies have explored the use of chemotherapy in the elderly (53)(54)(55)(56). The ELVIS trial demonstrated that single agent vinorelbine increased survival and quality of life over best supportive care (53).…”
Section: Clinical Protocolsmentioning
confidence: 99%
“…Response rate was 29% versus 10.9%, respectively. However, grade 3-4 hematologic toxicities and treatment-related deaths were significantly more frequent in patients treated with carboplatin and paclitaxel as compared to single-agent gemcitabine or vinorelbine [14]. Another phase III randomized trial enrolled 181 patients, aged > 70 years and with PS < 2, to receive two doublets, carboplatin (AUC 5 on day 1) plus gemcitabine (1250 mg/m on day 1 and 8) or paclitaxel (175 mg/m on day 1), every 3 weeks for a maximum of 4 cycles.…”
Section: Platinum-based Regimensmentioning
confidence: 97%
“…Finally, the first phase 3 randomised trial of platinum-based doublet therapy in an elderly population, presented in the plenary session of the 2010 ASCO meeting by the French Intergroup, addressed many issues raised by previous phase 2 trials [117]. This trial included 451 patients .70 yrs, and was closed at the second interim analysis since results greatly favoured weekly paclitaxel-monthly carboplatin doublet over the monotherapy arm (either vinorelbin or gemcitabine, depending on the choice of the centre).…”
Section: Elderly Patients Deserve Active Treatmentmentioning
confidence: 99%